Method for producing polyacrylamide with high molecular weight and high hydrolysis degree by adding alkali before homopolymerization
By using the homopolymerization pre-base addition method in the production of polyacrylamide, using sodium carbonate and a thermally sensitive sodium hydroxide hydrolyzer, a polyacrylamide product with high molecular weight and high hydrolysis degree was achieved, and hydrolysis in the prior art was solved The problem of insufficient degree and molecular weight improves the flocculation capacity and solubility of the product, shortens the production cycle and reduces the cost.
Patent Information
- Application Number
- CN202411633732.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-10
AI Technical Summary
The existing polyacrylamide production process is difficult to achieve high molecular weight and high hydrolysis at the same time, and has poor uniformity and solubility, which affects its effectiveness in oil fields such as drilling.
Using the method of adding alkali before homopolymerization, sodium carbonate and heat-sensitive sodium hydroxide are used as hydrolyzers. Through the dual-stage initiation system and nitrogen suspension technology, the sodium hydroxide particles are evenly dispersed, the hydrolysis degree and molecular weight are enhanced, and the homopolymerization is combined with homopolymerization. The advantages of pre-base addition and post-base addition processes shorten production cycles and save equipment costs.
Polyacrylamide products with high molecular weight and high hydrolysis degree have been achieved, which improves the flocculation capacity and water solubility of the products, shortens the production cycle, reduces the equipment cost, and ensures the uniformity and efficiency of the products.
Smart Images

Figure CN119285824A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyacrylamide preparation, and particularly relates to a method for producing high-molecular-weight and high-hydrolysis-degree polyacrylamide by adding alkali before homopolymerization. Background Art
[0002] Polyacrylamide (PAM) is a general term for acrylamide (AM) homopolymers or linear polymers obtained by copolymerization of acrylamide and other monomers. It is one of the most widely used water-soluble polymers. In industry, any polymer containing more than 50% acrylamide monomer is generally referred to as polyacrylamide. Polymers containing less than 5% of other monomer structural units are generally considered homopolymers of polyacrylamide.
[0003] In oil production, polyacrylamide is mainly used to improve the recovery rate and drilling mud materials, and is widely used in oil field production operations such as drilling, cementing, fracturing, and enhanced oil recovery. It has the functions of viscosity increase, filtration loss reduction, rheological adjustment, gelation, diversion, and profile adjustment. By injecting polyacrylamide aqueous solution, the oil-water flow rate ratio can be improved, and the crude oil content in the produced material can be greatly increased, thereby achieving the purpose of oil displacement. Among them, when polyacrylamide is used as a drilling fluid flocculant, it can moderately flocculate the colloidal particles in the drilling fluid to increase the fluid flow force, or make the dispersed particles (poor quality soil, microparticles, drill cuttings, etc.) aggregate by flocculation, form flocs and precipitate, so that the drilling fluid maintains a low solid phase state. At the same time, it also has a coating effect, which can coat the dispersed particles, so that the drill cuttings are not dispersed, easy to remove, and have an anti-collapse effect.
[0004] When polyacrylamide is used as a drilling fluid flocculant, its flocculation ability is determined by the product molecular weight and degree of hydrolysis. The higher the molecular weight of the polymer, the stronger the polymer adsorption and bridging effect; the higher the degree of polymer hydrolysis, the more extended the molecular chain, the more obvious the charge adsorption effect, and the stronger the flocculation ability. Therefore, there is an urgent need to synthesize a high molecular weight and high hydrolysis degree polyacrylamide product.
[0005] At present, the production process of polyacrylamide is divided into three categories: adding alkali before homopolymerization, adding alkali after homopolymerization and acrylamide copolymerization. The process of adding alkali before homopolymerization generally uses soda ash as a hydrolyzing agent, but the solubility of soda ash in acrylamide monomer solution is limited and is greatly affected by temperature. The hydrolysis degree range of the products that can be produced is small, generally not exceeding 30%. For products with higher hydrolysis degree, such as more than 35%, most manufacturers use post-hydrolysis production process, but there are disadvantages such as uneven product hydrolysis degree, poor solubility, high content of water-insoluble matter, long production process flow, high equipment investment and operating costs. Although the acrylamide copolymerization production process can produce ultra-high hydrolysis products, the molecular weight distribution range is wide, and the carboxylate block exists in the polymer, the water-insoluble matter is high, which affects the application performance of the product, and the molecular weight of the product tends to decrease with the increase of sodium acrylate content. Summary of the invention
[0006] The object of the present invention is to provide a method for producing high molecular weight and high hydrolysis degree polyacrylamide by adding alkali before homopolymerization.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a method for producing high molecular weight and high hydrolysis degree polyacrylamide by adding alkali before homopolymerization, comprising the following steps:
[0008] (1) adding 25-30 wt % of acrylamide crystals and 11-20 wt % of a hydrolyzing agent to 50-63 wt % of deionized water to dissolve the mixture under stirring; after being fully mixed, pumping the mixture into a polymerization reactor, cooling the mixture to 4-10° C., adding 0.05-0.15 wt % of azobisisobutyl cyanide to the reaction system, 0.004-0.01 wt % of a chain transfer agent to the reaction system, and 0.0004-0.001 wt % of a complexing agent to the reaction system, and introducing high-purity nitrogen to uniformly suspend the azobisisobutyl cyanide initiator and the hydrolyzing agent to obtain a transparent or translucent homopolymer solution;
[0009] (2) After passing high-purity nitrogen for 30 minutes, add 0.0001-0.0008wt% of oxidant, 0.0002-0.0007wt% of reducing agent and 0.1wt% of ammonia to the reaction system, the solution becomes thick and polymerizes, and the nitrogen is continued to be passed. When the viscosity of the system reaches 1500mpa·s, the nitrogen blowing is stopped and the polymerization is carried out under pressure. At this time, the whole system is in a viscous state, and the excess hydrolyzing agent and the azo initiator are evenly dispersed. After the polymerization is completed, it is hydrolyzed at 75-85°C for 6-12h to obtain a translucent or white elastic rubber block. The rubber block is taken out, granulated, dried, crushed and sieved to obtain a high molecular weight and high hydrolysis degree polyacrylamide with a molecular weight of 28 million and a hydrolysis degree of 45%.
[0010] Furthermore, in step (1), the hydrolyzing agent is a mixture of sodium carbonate and sodium hydroxide, the mass ratio of sodium carbonate to sodium hydroxide is 2:1, and the sodium hydroxide particles are coated with a layer of heat-sensitive material.
[0011] Furthermore, the thermosensitive material is a surfactant, specifically one of sorbitan fatty acid ester and fatty acid glyceride, such as Span 20, Span 40, Span 60, Span 80, glyceryl monostearate, triglycerol oleate, etc.
[0012] Furthermore, the method for coating the sodium hydroxide particles with a heat-sensitive material is as follows: adding the sodium hydroxide particles to the heat-sensitive material in a molten state (above 60° C.), rapidly stirring, filtering through a 100-mesh sieve, and cooling the temperature to room temperature to form a solid coating attached to the surface of the sodium hydroxide particles.
[0013] Furthermore, the chain transfer agent in step (1) is one of isopropanol, mercaptan, hypophosphite and sodium formate.
[0014] Furthermore, in the step (1), the complexing agent is EDTA-Na.
[0015] Furthermore, in step (2), the oxidant is an organic peroxide, and the reducing agent is one of potassium sulfite, sodium sulfite, sodium bisulfite, and triethanolamine; after adding the azo initiator, the oxidant, and the reducing agent, ammonia is continuously added to improve the water solubility of the product.
[0016] The present invention adopts the method of adding alkali before homopolymerization, which has the following characteristics:
[0017] ① The polymerization initiation system is highly active. This polymerization system adopts "double-stage initiation". In the early stage, it is a redox initiation system with extremely high activity, which causes the solution to thicken and polymerize quickly. The system temperature rises to the specified range within the specified time to prevent the suspended particles from sinking; in the later stage, azo initiators are used for secondary initiation until the system is fully polymerized.
[0018] ② The two hydrolyzing agents (sodium carbonate and sodium hydroxide) are effectively combined to make the hydrolysis more thorough. Industrial sodium carbonate is a white powder and is a commonly used hydrolyzing agent for the pre-alkaline polymerization of acrylamide. As the polymerization temperature increases, the hydrolysis reaction gradually occurs, but due to the solubility of the system, the room for improving the hydrolysis degree of the product is limited, and generally does not exceed 30%; while sodium hydroxide is a white granular strong base. If it is directly added to the system, it can immediately react with acrylamide to hydrolyze, affecting the later polymerization process. Therefore, a layer of heat-sensitive material is wrapped on the surface of the sodium hydroxide particles. After the system is fully deoxygenated, the initiator is added, and nitrogen is continuously introduced. When the solution thickens to a certain degree, the sodium hydroxide particles can be evenly distributed in the rubber block. As the polymerization temperature increases (over 60°C), the heat-sensitive material liquefies, and the polymerized rubber block directly contacts the sodium hydroxide particles, and a hydrolysis reaction occurs, and the product hydrolysis degree is further improved. The method combines the alkali addition process before homopolymerization with the alkali addition process after homopolymerization, which not only retains the hydrolysis process of the alkali addition before and avoids the influence of sodium hydroxide on the materials in the early stage of polymerization, but also evenly disperses the sodium hydroxide particles in the polymerization system, realizes the effect of the alkali addition process after homopolymerization, improves the hydrolysis degree of the product and achieves the purpose of increasing the molecular weight of the polymer.
[0019] ③ Compared with other production processes, the conventional alkali addition process before homopolymerization is easily limited by the solubility of soda ash. If you want to increase the hydrolysis degree, you need to increase the amount of soda ash, which will invisibly increase the initial polymerization temperature, resulting in a decrease in the product molecular weight, and it is difficult to achieve a hydrolysis degree of more than 30%; although the hydrolysis process after homopolymerization can greatly increase the product hydrolysis degree, it is affected by the addition of alkali during the first granulation, and it is difficult to mix the rubber block and the granular alkali, resulting in insufficient hydrolysis, uneven distribution of product hydrolysis degree, poor solubility, and reduced viscosity. At the same time, the secondary granulation causes serious loss of product molecular weight due to shearing of the rubber block; the copolymerization production process of sodium acrylate and acrylamide can produce products with ultra-high hydrolysis degree, but the molecular weight distribution range is wide, and the carboxylate block exists in the polymer, and the water-insoluble matter is high, which affects the application performance of the product. The product molecular weight tends to decrease with the increase of sodium acrylate content.
[0020] The method of the present invention is an effective combination of a pre-homopolymerization alkali addition process and a post-hydrolysis process. At a relatively low temperature, a hydrolyzing agent is selected from a mixture of sodium carbonate and sodium hydroxide, wherein sodium hydroxide particles are wrapped by a layer of heat-sensitive material and suspended in an aqueous solution in the form of insoluble particles at the initial polymerization temperature; after the initiator is added, nitrogen is passed until the system thickens to a certain degree (1500mpa·s), ensuring that the sodium hydroxide particles are uniformly dispersed in the system during the polymerization process, which is convenient for post-hydrolysis. Under the premise of ensuring product quality, the production cycle is shortened, equipment costs are saved, and the product molecular weight and hydrolysis degree are maximized. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The curve of hydrolysis degree of sodium carbonate as hydrolyzing agent in 25% acrylamide aqueous solution is plotted against temperature. DETAILED DESCRIPTION
[0022] The following are specific embodiments of the present invention, which further describe the technical solution of the present invention, but the protection scope of the present invention is not limited to these embodiments. Any changes or equivalent substitutions that do not deviate from the concept of the present invention are included in the protection scope of the present invention.
[0023] Example 1
[0024] Calculate the materials required for 3 / 4 volume of the polymerization kettle, add 25wt% of acrylamide crystals (hereinafter all are mass percentages) accounting for the reaction system and 12wt% of the hydrolyzing agent accounting for the reaction system into a modulation kettle containing 62.7435wt% of deionized water accounting for the reaction system under stirring to dissolve, mix thoroughly, pump into the polymerization kettle, cool to 10°C, add 0.15wt% of azobisisobutyl cyanide accounting for the reaction system, 0.005wt% of chain transfer agent isopropanol accounting for the reaction system and 0.0005wt% of complexing agent EDTA-Na accounting for the reaction system, introduce high-purity nitrogen to make the azobisisobutyl cyanide initiator and excess sodium bicarbonate in a uniform suspension state, and obtain a transparent or translucent homopolymer liquid.
[0025] Wherein, the hydrolyzing agent is a mixture of sodium carbonate and sodium hydroxide, the mass ratio of sodium carbonate: sodium hydroxide is 2:1, the sodium hydroxide particles are wrapped by a layer of heat-sensitive material, the heat-sensitive material is glyceryl monostearate, the sodium hydroxide particles are added to the glyceryl monostearate in a molten state, stirred rapidly, filtered through a 100-mesh sieve, and after the temperature is reduced to room temperature, a solid coating is formed on the surface of the sodium hydroxide particles.
[0026] Figure 1 The figure shows the change of the hydrolysis degree of sodium carbonate in a 25% aqueous solution of acrylamide with temperature. It can be seen from the figure that the hydrolysis degree increases with temperature. In a solution without any precipitation, the curve represents the highest alkaline hydrolysis degree that sodium carbonate can obtain at a certain temperature. The lower part of the curve represents the area where sodium carbonate is completely dissolved, and the upper part represents the precipitation and precipitation of sodium carbonate. Therefore, the operator can determine whether the hydrolysis agent is excessive by the rapid formation of precipitation at a certain temperature.
[0027] High-purity nitrogen was passed for 30 minutes, and then 0.0005wt% of the oxidant, 0.0005wt% of the reducing agent sodium sulfite, and 0.1wt% of the ammonia were added to the reaction system. The solution became thick and polymerized. Nitrogen was continued to be passed until the viscosity of the system reached 1500mpa·s, and nitrogen was stopped. The polymerization was carried out under pressure. At this time, the whole system was viscous, and the excess hydrolyzing agent and azo initiator were evenly dispersed. After the polymerization was completed, it was hydrolyzed at 80℃ for 6h to obtain a translucent or white elastic rubber block.
[0028] The rubber block is taken out, granulated, dried, crushed and sieved to obtain a product with 20-100 mesh, 89% solid content, 28.89 million molecular weight and 45.8% hydrolysis degree. Such a high hydrolysis degree is achieved by liquefying the heat-sensitive material wrapped in sodium hydroxide after the polymerization reaction is completed, and the sodium hydroxide particles continue to hydrolyze the rubber block.
[0029] Example 2
[0030] Calculate the materials required for 3 / 4 volume of the polymerization kettle, add 29.8987wt% of acrylamide crystals (hereinafter all are mass percentages) accounting for 29.8987wt% of the reaction system and 20wt% of the hydrolyzing agent accounting for 20wt% of the reaction system into a modulation kettle containing 50wt% of deionized water under stirring to dissolve, mix thoroughly, pump into the polymerization kettle, cool to 8°C, add 0.09wt% of azobisisobutyl cyanide accounting for 0.01wt% of the reaction system, 0.001wt% of the chain transfer agent hypophosphite accounting for 0.001wt% of the reaction system and EDTA-Na accounting for 0.001wt% of the reaction system, introduce high-purity nitrogen to make the azobisisobutyl cyanide initiator and excess sodium bicarbonate in a uniform suspension state, and obtain a transparent or translucent homopolymer liquid.
[0031] The hydrolyzing agent is a mixture of sodium carbonate and sodium hydroxide, the mass ratio of sodium carbonate to sodium hydroxide is 2:1, the sodium hydroxide particles are wrapped by a layer of heat-sensitive material, the heat-sensitive material is Span 80, the sodium hydroxide particles are added to the molten Span 80, stirred rapidly, filtered through a 100-mesh sieve, and after the temperature is reduced to room temperature, a layer of solid coating is formed on the surface of the sodium hydroxide particles.
[0032] High-purity nitrogen was passed for 30 minutes, and then 0.0001wt% of the oxidant, 0.0002wt% of the reducing agent potassium sulfite, and 0.1wt% of the ammonia were added to the reaction system. The solution became thick and polymerized. Nitrogen was continued to be passed until the viscosity of the system reached 1500mpa·s, and nitrogen was stopped. The polymerization was carried out under pressure. At this time, the whole system was viscous, and the excess hydrolyzing agent and azo initiator were evenly dispersed. After the polymerization was completed, it was hydrolyzed at 75℃ for 8h to obtain a translucent or white elastic rubber block.
[0033] The rubber block is taken out, granulated, dried, crushed and sieved to obtain a product with 20-100 mesh, 88% solid content, 28.41 million molecular weight and 45.3% hydrolysis degree.
[0034] Example 3
[0035] Calculate the materials required for 3 / 4 volume of the polymerization kettle, add 25.9437wt% of acrylamide crystals (hereinafter all are mass percentages) accounting for 25.9437wt% of the reaction system and 11wt% of the hydrolyzing agent accounting for 11wt% of the reaction system into a modulation kettle containing 63wt% of deionized water under stirring to dissolve, mix thoroughly, pump into the polymerization kettle, cool to 4°C, add 0.05wt% of azobisisobutyl cyanide accounting for 0.004wt% of the reaction system, chain transfer agent sodium formate accounting for 0.0008wt% of the reaction system and complexing agent EDTA-Na accounting for 0.0008wt% of the reaction system, introduce high-purity nitrogen to make the azobisisobutyl cyanide initiator and excess sodium bicarbonate in a uniform suspension state, and obtain a transparent or translucent homopolymer liquid.
[0036] The hydrolyzing agent is a mixture of sodium carbonate and sodium hydroxide, the mass ratio of sodium carbonate to sodium hydroxide is 2:1, the sodium hydroxide particles are wrapped by a layer of heat-sensitive material, the heat-sensitive material is triglycerol oleate, the sodium hydroxide particles are added to Span 80 in a molten state, stirred rapidly, filtered through a 100-mesh sieve, and after the temperature is reduced to room temperature, a solid coating is formed on the surface of the sodium hydroxide particles.
[0037] High-purity nitrogen was passed for 30 minutes, and then 0.0008wt% of the oxidant, 0.0007wt% of the reducing agent triethanolamine, and 0.1wt% of the ammonia were added. The solution became thick and polymerized. Nitrogen was continued to be passed until the viscosity of the system reached 1500mpa·s, and nitrogen was stopped. The polymerization was carried out under pressure. At this time, the whole system was viscous, and the excess hydrolyzing agent and azo initiator were evenly dispersed. After the polymerization was completed, it was hydrolyzed at 85℃ for 12h to obtain a translucent or white elastic rubber block.
[0038] The rubber block is taken out, granulated, dried, crushed and sieved to obtain a product with 20-100 mesh, solid content of 90%, molecular weight of 28.6 million and hydrolysis degree of 45.5%.
[0039] Example 4
[0040] Calculate the materials required for 3 / 4 volume of the polymerization kettle, add 30wt% of acrylamide crystals (hereinafter all are mass percentages) accounting for the reaction system and 17wt% of the hydrolyzing agent accounting for the reaction system into a modulation kettle containing 52.9206wt% of deionized water accounting for the reaction system under stirring to dissolve, mix thoroughly, pump into the polymerization kettle, cool to 6°C, add 0.07wt% of azobisisobutyl cyanide accounting for the reaction system, 0.008wt% of the chain transfer agent mercaptan accounting for the reaction system and 0.0006wt% of the complexing agent EDTA-Na accounting for the reaction system, introduce high-purity nitrogen to make the azobisisobutyl cyanide initiator and excess sodium bicarbonate in a uniform suspension state, and obtain a transparent or translucent homopolymer liquid.
[0041] The hydrolyzing agent is a mixture of sodium carbonate and sodium hydroxide, the mass ratio of sodium carbonate to sodium hydroxide is 2:1, the sodium hydroxide particles are wrapped by a layer of heat-sensitive material, the heat-sensitive material is Span 60, the sodium hydroxide particles are added to Span 80 in a molten state, stirred rapidly, filtered through a 100-mesh sieve, and after the temperature is reduced to room temperature, a layer of solid coating is formed on the surface of the sodium hydroxide particles.
[0042] High-purity nitrogen was passed for 30 minutes, and then 0.0004wt% of the oxidant, 0.0004wt% of the reducing agent sodium bisulfite, and 0.1wt% of the ammonia were added to the reaction system. The solution became thick and polymerized. Nitrogen was continued to be passed until the viscosity of the system reached 1500mpa·s, and nitrogen was stopped. The polymerization was carried out under pressure. At this time, the whole system was viscous, and the excess hydrolyzing agent and azo initiator were evenly dispersed. After the polymerization was completed, it was hydrolyzed at 80℃ for 10h to obtain a translucent or white elastic rubber block.
[0043] The rubber block is taken out, granulated, dried, crushed and sieved to obtain a product with 20-100 mesh, 89% solid content, 28.98 million molecular weight and 45.9% hydrolysis degree.
[0044] Comparative Example 1
[0045] The steps of Example 1 were repeated, except that the sodium hydroxide in the hydrolyzing agent was removed. The hydrolyzing agent was sodium carbonate accounting for 12 wt% of the reaction system. The hydrolyzing agent was completely dissolved. The final polymer obtained had a hydrolysis degree of 35.9% and a molecular weight of 26.57 million.
[0046] This comparative example illustrates that the sodium hydroxide in the present invention plays an irreplaceable role in improving the hydrolysis degree of the product.
[0047] Comparative Example 2
[0048] The steps of Example 1 were repeated, except that the heat-sensitive material wrapping the sodium hydroxide particles was removed. The results showed that there was no abnormality in the polymerization process, but the rubber block after polymerization was soft and sticky and could flow slowly, making it impossible to implement the subsequent granulation process, affecting normal production.
[0049] This comparative example shows that the system presents a strong alkaline environment after the addition of liquid alkali, which can promote the partial hydrolysis reaction of AM and affect the polymerization on the one hand; on the other hand, the hydroxide has chain transfer properties, and the presence of a large number of hydroxides reduces the molecular weight of the product, and the rubber block appears soft and sticky.
[0050] Comparative Example 3
[0051] In order to verify the influence of the distribution of sodium hydroxide particles in the system on the product, we repeated the steps of Example 1 and added oxidizing and reducing agents, but the difference was that the nitrogen blowing was stopped before the solution became thick, so that the sodium hydroxide particles were sunk to the bottom of the polymerization container, and the same test sample was tested in parallel for multiple times. The results are as follows:
[0052] Test No. Molecular weight Solubility Degree of hydrolysis Parallel 1 27.89 million excellent 35.50% Parallel 2 26.93 million excellent 48.81%
[0053] This comparative example shows that the sodium hydroxide particles sink to the bottom of the rubber block, and the product hydrolysis degree index is difficult to increase significantly. In addition, as the polymerization temperature increases, the heat-sensitive material wrapped with the sodium hydroxide particles at the bottom of the rubber block liquefies, causing further hydrolysis reaction on the rubber block, increasing the product hydrolysis degree and causing fluctuations in product quality.
[0054] The present invention is not limited to the above-mentioned implementation modes, and anyone should be aware of the structural changes made under the enlightenment of the present invention, and all those having the same or similar technical solutions as the present invention fall within the protection scope of the present invention.
[0055] The techniques, shapes, and structural parts not described in detail in the present invention are all well-known techniques.
Claims
1. A method for producing high molecular weight and high hydrolysis degree polyacrylamide by adding alkali before homopolymerization, characterized in that: The following steps are involved: (1) adding 25-30 wt % of acrylamide crystals and 11-20 wt % of a hydrolyzing agent to 50-63 wt % of deionized water to dissolve the mixture under stirring; after being fully mixed, pumping the mixture into a polymerization reactor, cooling the mixture to 4-10° C., adding 0.05-0.15 wt % of azobisisobutyl cyanide to the reaction system, 0.004-0.01 wt % of a chain transfer agent to the reaction system, and 0.0004-0.001 wt % of a complexing agent to the reaction system, and introducing high-purity nitrogen to uniformly suspend the azobisisobutyl cyanide initiator and the hydrolyzing agent to obtain a transparent or translucent homopolymer solution; (2) After passing high-purity nitrogen for 30 minutes, add 0.0001-0.0008wt% of oxidant, 0.0002-0.0007wt% of reducing agent and 0.1wt% of ammonia to the reaction system, the solution becomes thick and polymerizes, and the nitrogen is continued to be passed. When the viscosity of the system reaches 1500mpa·s, the nitrogen blowing is stopped and the polymerization is carried out under pressure. At this time, the whole system is in a viscous state, and the excess hydrolyzing agent and the azo initiator are evenly dispersed. After the polymerization is completed, it is hydrolyzed at 75-85°C for 6-12h to obtain a translucent or white elastic rubber block. The rubber block is taken out, granulated, dried, crushed and sieved to obtain a high molecular weight and high hydrolysis degree polyacrylamide with a molecular weight of 28 million and a hydrolysis degree of 45%.
2. The method for producing high molecular weight and highly hydrolyzed polyacrylamide by adding alkali before homopolymerization as claimed in claim 1, characterized in that: In the step (1), the hydrolyzing agent is a mixture of sodium carbonate and sodium hydroxide, the mass ratio of sodium carbonate to sodium hydroxide is 2:1, and the sodium hydroxide particles are wrapped by a layer of heat-sensitive material.
3. The method for producing high molecular weight and highly hydrolyzed polyacrylamide by adding alkali before homopolymerization as claimed in claim 2, characterized in that: The heat-sensitive material is a surfactant, specifically one of sorbitan fatty acid ester and fatty acid glyceride.
4. The method for producing high molecular weight and highly hydrolyzed polyacrylamide by adding alkali before homopolymerization as claimed in claim 2, characterized in that: The method for coating the sodium hydroxide particles with a heat-sensitive material is as follows: adding the sodium hydroxide particles to the heat-sensitive material in a molten state, rapidly stirring, filtering with a 100-mesh screen, and cooling the temperature to room temperature to form a solid coating attached to the surface of the sodium hydroxide particles.
5. The method for producing high molecular weight and highly hydrolyzed polyacrylamide by adding alkali before homopolymerization as claimed in claim 1, characterized in that: The chain transfer agent in step (1) is one of isopropanol, mercaptan, hypophosphite and sodium formate.
6. The method for producing high molecular weight and highly hydrolyzed polyacrylamide by adding alkali before homopolymerization as claimed in claim 1, characterized in that: In the step (1), the complexing agent is EDTA-Na.
7. The method for producing high molecular weight and highly hydrolyzed polyacrylamide by adding alkali before homopolymerization as claimed in claim 1, characterized in that: In the step (2), the oxidant is an organic peroxide, and the reducing agent is one of potassium sulfite, sodium sulfite, sodium bisulfite, and triethanolamine.
Citation Information
Cited By
Preparation method of salt-resistant high-temperature-resistant quick-response polyacrylamide flocculant
CN122608813A